CLINICAL STUDIES OF REACTOGENICITY, SAFETY AND IMMUNOGENICITY OF LIVE MONOVALENT INFLUENZA VACCINE (STRAIN А/17/CALIFORNIA/2009/38 — H1N1) IN CHILDREN - D.S. Bushmenkov; A.N. Mironov; A.A. Romanova; A.A. Tsaan; I.V. Feldblyum (Вопросы современной педиатрии)
Results of performed pre-clinical and clinical studies with volunteers 18-60 years old allowed registration of vaccine «INFLUVIR» (live monovalent vaccine for the prophylaxis of influenza A/H1N1, strain A/17/California/2009/38 (H1N1), developed by NPO «Microgen» in Russian Federation so timely vaccination campaign was performed. As a result, the level of morbidity with influenza A/H1N1 in Russia was decreased, and development of complication was prevented. Clinical studies in different groups of children were performed for the purpose of widening indications for vaccine «INFLUVIR» administration. According to the results of studies vaccine «INFLUVIR» has good tolerability and safety, low reactogenicity, and significant immunogenicity. This fact will allow changing of present normative documentation and administration of «INFLUVIR» in children of different age for prophylaxis of influenza A/H1N1.Key words: children, influenza, virus A/H1N1, live influenza vaccine, tolerability, safety, immunogenicity.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):101-105)